Lithotype composition and micro-topographic features: Drivers of soil variability on semiarid limestone plateaus - de Oliveira, Daniel Pontes; Bovi, Renata Cristina [UNESP]; Castilho, Yuri Fernando Parra; de Souza Júnior, Valdomiro Severino; Cooper, Miguel; Queiroz, Hermano Melo; Corrêa, Marcelo Metri; Romero, Ricardo Espíndola; Ferreira, Tiago Osório (Elsevier, 2024)
Different soil classes indicate that pedoenvironments undergo varied formation conditions. Among the soil formation factors, relief is predominantly employed in predicting soil distribution at a landscape, guided by the catena concept, where soils are genetically linked from the summit to a footslope. The relationship between soil classes and relief emphasizes the importance of understanding the landscape's topography in driving distribution and characteristics of different soils. This study aims to unravel the combined role of limestone composition and microrelief in soils pedogenesis through morphological, chemical, physical, mineralogical, and micromorphological attributes of a six soil profiles sequence. The topography of the study area on the Apodi Plateau was examined, exposing variations in surface relief classified as convex, flat, and concave. Furthermore, two limestone samples were collected at different points on the concave and convex surfaces for chemical characterization. The chemical and morphological results indicate that the soils on the concave surface are more weathered and developed, evidenced by the depth, a low ki index (mean ± s.d.: 1.8 ± 0.5), low clay activity values (54.62), and lower contents of crystalline iron (mean ± s.d.: 3.7 ± 0.6 g kg−1) and CaCO3 (mean ± s.d.: 20.7 ± 17.8 g kg−1). Micromorphological analyses revealed that the pedality and accommodation degree of the aggregates increase towards the concave surface, indicating more active pedogenesis. The variation in the related distribution pattern from convex to concave surfaces can be an indication of distinct pedogenesis. Observations on convex and flat surfaces revealed carbonate nodules and CaCO3 depletion, suggesting a favorable environment for carbonate precipitation due to lower water action. The concave surface exhibited higher weathering rates on a local scale, influenced by microrelief and predominant water flow. The weathering-susceptible limestone with increased insoluble residues in this area conditions the development of a more advanced soil in the concave surface.
Keywords: Differential pedogenesis; Limestone composition; Limestone plateau; Microrelief